(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
Cardiovascular diseases and atherosclerosis remain the same cause of disability and mortality in the world. Study of vascular dysfunction of the vascular endothelium and hyperlipoproteinemia in experimental atherosclerosis. The experiment was carried out on 28 rabbits with an average chinchilla weight of 2.5-3.0 kg. The effect of the drug is clear and dynamic: the first 3 months and 1 month after the first dose. The results obtained were compared with the results of the control and intact groups. Long-term use of cholesterol is accompanied by the development of hypertriglyceridemia , the effect of which depends on the duration of the experiment. An important role in the development of endothelial dysfunction in hypercholesterolemia is played by a decrease in the synthesis of endothelial nitric oxide and an increase in its active radicals, modification of low-density lipoproteins and their deposition in the vascular endothelium.